Probabilistic Seismic Hazard Analysis for Nepal - P.M Pradhan; S.P Timalsina; M.R Bhatt (International Association of Lowland Technology, 2020)
Nepal lies in the zone of Himalayan belt formed due to collision oftwo continental plates and have the high probability of earthquakeoccurrence. Many destructive earthquakes have been reported inpast causing the massive destruction of lives and property. Forreducing the risks caused by seismic events, proper study shouldbe carried out beforehand, one of which is seismic hazard analysis.In this study, Probabilistic Seismic Hazard Analysis (PSHA) iscarried out for Nepal and the hazard map is prepared in terms ofPeak Horizontal Acceleration (PHA) for 500 years return period atbedrock level. The available earthquake catalogue for Nepal isprocessed for magnitude homogeneity and removal of aftershocks.The seismicity parameters are obtained using the method obtainedfor multiple catalogs with different level of completeness. The areasource models are used for the analysis since the earthquakedistribution is diffused and no particular information on faults isavailable. The attenuation relationship available for subductionzone earthquake is used for determining the PHA at a particularsite. The software CRISIS2007 is used for computing andpreparing hazard map for Nepal. The map is divided into numberof sites using grids of 0.1o by 0.1o and PHA value at each grid iscomputed, finally, obtaining the hazard map for Nepal. The hazardmap shows that the PHA value varies from 0.09g to 0.5g for Nepal,with the maximum values at Eastern and Western part of Nepal.This high level of seismicity in the regions shows that the properplans should be implemented for reducing the risks caused byseismic events, like earthquake resistant design of structures